Remote Control of Experiments via Matlab - Zakova, Katarina; Sedlak, Michal (International Journal of Online and Biomedical Engineering (iJOE), 2006)
The paper demonstrates two possibilities of remote control of real experiments using Matlab software environment. We introduced basic approaches to Matlab remote access using Matlab Web Server, COM and Virtual Reality Toolbox. The proposed concepts were used and tested for control of magnetic levitation system. The gained experience was also discussed in the paper.